A Study of Integrative Islamic Thought on the Relationship between Fiqh and Sufism - Muhammad Ni'amul Hikam; Ghailaan Aufaa Majid; Ifna Kirana Diva; Khijwa Salma Khodijah; Naka Prayogi; Khoirunnisa Fadilatul Aeni (TATHO: International Journal of Islamic Thought and Sciences, 2026)
This qualitative research is in the form of a literature study and content analysis of Buya Yahya's thoughts on the relationship between fiqh and Sufism. According to Buya Yahya himself, the science of Sufism must be based on the science of fiqh, because the science of Sufism without studying fiqh is called zindiq (disbelief). Meanwhile, learning the science of fiqh without the science of Sufism is called tafasakh (broken). This research confirms that the relationship between Sufism and fiqh must go hand in hand so that the decisions taken are balanced between human and divine values. With this understanding, it will form a more responsible person so that a person does not only lean towards sharia law, but also has an inner awareness. Jurisprudence explains clear rules on how a Muslim should behave, while Sufism helps to implement these rules with a clean and sincere heart